Exploring the Experiential Journey of Women with PCOS Across the Lifespan: A Qualitative Inquiry - Wright PJ; Dawson RM; Corbett CF (Dove Medical Press, 2024)
Pamela J Wright, Robin M Dawson, Cynthia F Corbett Advancing Chronic Care Outcomes through Research and iNnovation (ACORN) Center, Department of Biobehavioral Health & Nursing Science, College of Nursing, University of South Carolina, Columbia, SC, USACorrespondence: Pamela J Wright, Department of Biobehavioral Health & Nursing Science, College of Nursing, University of South Carolina, 1601 Greene Street, Columbia, SC, 29208, USA, Tel +1-803-777-6039, Email wrightpamelaj@sc.eduIntroduction: Peri-postmenopausal women with the chronic condition polycystic ovary syndrome (PCOS) remain at cardiometabolic risk and/or subsist with established comorbidity while continuing to manage persistent PCOS signs and symptoms, such as hirsutism. Thus, PCOS transcends the reproductive years, yet there is sparse scientific literature on the peri-postmenopausal years of women with PCOS.Purpose: To explore how peri-postmenopausal women's perceptions about PCOS have changed over the lifespan since their PCOS diagnosis.Methods: A cross-sectional survey with one qualitative question was conducted via Research Electronic Data Capture (REDCap) among women with PCOS aged ≥ 43 years, who were all recruited from PCOS-specific Facebook pages. Of the 107 women completing the survey, 72 substantively answered the qualitative question. The qualitative responses were analyzed using the steps of reflexive thematic analysis. Themes were interpreted and discussed through the lens of the bioecological conceptual model.Results: Respondents were 47.6 (± 4.1) years of age, primarily White (87.5%), employed full time (65.3%), and married (75%) with children (68%). Four overall themes were identified: 1) dismissal 2) information desert, 3) PCOS experience over the lifespan, and 4) mindset.Conclusion: The study findings illustrated the unique healthcare needs among peri-postmenopausal women with PCOS. Further research is needed to further explore their healthcare concerns and psychosocial needs followed by studies that develop and assess interventions that promote symptom and adaptive coping strategies across their lifespan.Keywords: polycystic ovary syndrome, systems theory, life course, women's health